Oxidative Stress And Its Association With Cardio Vascular Risk In Acute Renal Failure - G.RAMANI; G.KAVITHA; PRIYA K DHASS; DR.RITA MARY ARUNA (International Journal of Pharma and Bio Sciences, 2011)
Acute renal failure (ARF) is a clinical syndrome in which there is a rapid decrease in the kidney function. Underlying renal disease itself leads to elevated formation of reactive oxygen species which is shown to have an active role in pathogenesis of renal disease. Oxidative stress reduces Total antioxidant status and is implicated in atherogenesis. Patients with Acute renal failure are often prone for cardiovascular disease. Oxidative stress and a subclinical inflammation are crucial factors in its development. The aim of the present study is focused on the association of oxidative stress and atherogenic index in acute renal failure. This study includes 62 patients with ARF and 50 healthy individuals as controls. The levels of Blood urea, Serum creatinine, serum Triglycerides, Total cholesterol, LDL cholesterol, VLDL cholesterol, MDA and Total antioxidant capacity were analyzed with fasting blood sample using standard methods in patients with ARF and controls. TC/HDL, LDL/HDL ratio, atherogenic index of plasma, MDA/TAC ratio were calculated. A significant decrease in TAC and increase in MDA were found in patients with ARF compared to controls. Serum creatinine showed significant correlation with HDL- cholesterol, atherogenic index of plasma and MDA/TAC ratio. Hence the study may be useful in designing clinical studies that target utilizing antioxidant systems to provide protective pathways on the pathogenesis of renal failure.